Research on Non Elite Groups in Ancient Egypt from the Perspective of Material Culture - Tao, Shuhan (Transactions on Social Science, Education and Humanities Research, 2026)
The historical narrative of traditional Egyptology has long been centered around pharaohs, priests, and high-ranking officials, with the vast majority of the ancient Egyptian population consisting of farmers, craftsmen, and ordinary laborers who have almost lost their voice in historical writing due to a lack of written records. This article summarizes the main progress in the study of non elite groups in ancient Egypt from the perspective of material culture. The article first sorted out three core material materials: settlement sites, tomb remains, and daily objects, and discussed their unique value and limitations in reconstructing the living world of ordinary people. On this basis, the article discusses from four dimensions: economic life, social stratification, faith practice, and cultural interaction. This article argues that the study of material culture not only provides a feasible way to write a more inclusive history of Egyptian society, but also promotes the development of Egyptology from elite history to social history, and from the center of literature to the interaction between things and people. However, this research path also faces practical challenges such as material preservation bias and interpretation methodology selection, and requires continuous improvement through interdisciplinary collaboration.
Keywords: Ancient Egypt; Non elite group; Material culture; Archaeology.